Transcriptional regulation of lipid metabolism and inflammation in transition dairy goats by fish oil and stearate (International Journal of Health, Animal Science and Food Safety, 2016)
To better understand the interaction between saturated or unsaturated fatty acids and its effect onexpression of genes involved in subcutaneous adipose tissue metabolism, 23 second parity alpine dairygoats were enrolled in the experiment and fed either a non fat-supplemented basal diet (C; n=8), thebasal diet supplemented with stearic acid (ST; n=7) or the basal diet supplemented with fish oil (FO;n=8). 30g/head/d supplemental fatty acids during the dry period and 50g/head/d during lactation weredelivered starting one week before parturition up to 21 days in milk. Subcutaneous adipose tissuesamples were harvested at day -7, 7 and 21 relative to kidding and mRNA levels of genes involved ininflammation were measured via qPCR. Data were analyzed using the MIXED procedure of SAS. Nosignificant effects for treatment were observed, however eight genes were significant for time. HP andSAA3 expression peaked at day 7 postpartum, to then return at prepartum level around 21 d relative tokidding, while IL8, IL10, and IL18 expression constantly increased along the transition period. Vice versa,expression of IL1β, IL6R, and RXRA decreased in response to kidding, with a subsequent increase at day21. The obtained results led us to hypothesize that goats face a postponed lipomobilization afterkidding, probably related to their reduced production. The next step will involve the analysis of miRNArelated to immune cell infiltration, adipocyte inflammation and lipolysis and positive regulation ofadipogenesis to better understand the complex network of lipid metabolism in periparturient goats.
Keywords: Goat; Lipidic metabolism; Inflammation; Gene expression; Peripartum; Adipose tissue; Lipidic integration